2001
DOI: 10.1073/pnas.091095998
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fos-Jun-NFAT1 complexes

Abstract: Transcription initiation in eukaryotes is controlled by nucleoprotein complexes formed through cooperative interactions among multiple transcription regulatory proteins. These complexes may be assembled via stochastic collisions or defined pathways. We investigated the dynamics of Fos-Jun-NFAT1 complexes by using a multicolor fluorescence resonance energy transfer assay. Fos-Jun heterodimers can bind to AP-1 sites in two opposite orientations, only one of which is populated in mature Fos-Jun-NFAT1 complexes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
50
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…This cooperative action has been well documented both for ETS-AP1 (8), ERG-AP1 (9), and more interestingly for EWSR1/ FLI1-AP1 (10) and NFAT-AP1 (25). It has been shown that both NFAT and ETS transcription factors interact with the bZIP motifs of the Fos-Jun complex (9,10,25,26). Intriguingly, when comparing the sequence recognition patterns of these two gene families (ETS and NFAT), an overlap of the core consensus sequence was observed.…”
Section: Discussionmentioning
confidence: 99%
“…This cooperative action has been well documented both for ETS-AP1 (8), ERG-AP1 (9), and more interestingly for EWSR1/ FLI1-AP1 (10) and NFAT-AP1 (25). It has been shown that both NFAT and ETS transcription factors interact with the bZIP motifs of the Fos-Jun complex (9,10,25,26). Intriguingly, when comparing the sequence recognition patterns of these two gene families (ETS and NFAT), an overlap of the core consensus sequence was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Assembly of these nucleoprotein complexes can be affected by the orientations of the individual regulatory elements (26,27,39,40). Some heterodimers that recognize palindromic DNA sequences also exhibit orientation-dependent transcriptional activities at regulatory elements that contain asymmetric base pairs either within the recognition site or in flanking sequences (6,10,35,36). This orientation dependence can be mediated by cooperative DNA binding with transcription factors that recognize adjacent binding sites within composite regulatory elements (10,35,36).…”
mentioning
confidence: 99%
“…Some heterodimers that recognize palindromic DNA sequences also exhibit orientation-dependent transcriptional activities at regulatory elements that contain asymmetric base pairs either within the recognition site or in flanking sequences (6,10,35,36). This orientation dependence can be mediated by cooperative DNA binding with transcription factors that recognize adjacent binding sites within composite regulatory elements (10,35,36).Fos and Jun family bZIP proteins form homo-and heterodimers via a leucine zipper dimerization interface and bind to palindromic AP-1 recognition elements [TGA(C/G)TCA] via a basic DNA contact region. Fos and Jun make essentially identical contacts with the two half-sites in the X-ray crystal structure of the Fos-Jun-AP-1 complex (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interactions between such heterodimers and transcription factors that bind adjoining sequences are generally thought to require a specific orientation of heterodimer binding. For instance, cooperative DNA binding by Fos-Jun, Fos-Activating Transcription Factor 2 (ATF2), 2 or ATF2-Jun heterodimers with Nuclear Factor of Activated T cells 1 (NFAT1) at composite regulatory elements imposes a fixed orientation of heterodimer binding (3)(4)(5)(6)(7). Differences in the preferred orientation of Fos-Jun heterodimer binding at different regulatory elements affect cooperative DNA binding and synergistic transcription activation with NFAT1 (6 -8).…”
mentioning
confidence: 99%